Innovative Design and Application of Huayao Cross-stitch Pattern in Women's Leather Bags - Huichao LIU; Yi ZHANG (Pige Kexue Yu Gongcheng)
Huayao cross-stitch pattern has various shapes and exquisite design, which has high aesthetic value and application value, but there are relatively few researches on its innovative application to the field of luggage design. From the point of view of design, this paper analyzed the typical patterns and cultural connotation of Huayao cross-stitch, and summarized the characteristics of its core elements. Investigation and analysis of consumer groups and their style preferences were conducted to establish the product design positioning. We selected typical cross-stitch patterns, used shape grammar and style transfer algorithm to carry out innovative redesign respectively, and combined with 3D digital software to apply the innovative scheme to fashion women's bag design, and developed both national characteristics and modern form of beauty leather products. Through the organic combination of digital technology and Huayao cross-stitch pattern leather goods, it not only guarantees the iteration and innovation of cross-stitch pattern, but also improves the creation efficiency of leather product pattern design.